Exploiting the Synergy between Automated-Test-Generation and Programming-by-Contract - Barnett, Mike; Fahndrich, Manuel; Halleux, Jonathan "Peli" de; Logozzo, Francesco; Tillmann, Nikolai (Proc. 31st International Conference on Software Engineering (ICSE'2009), 2009)
This demonstration presents two tools, Code Contracts and Pex, that utilize specification constructs for advanced testing, runtime checking, and static checking of object-oriented .NET programs.
Research Demonstration